Membangun Rasa Empati Dan jiwa Sosial Di Era Digital - Nur Ashabul Khafi; Mega Mustika; Ahmad Nurfauzi Budiamin; Evi Tri Utami; Arham, Arham; Feri Eko Putra; Nur Ainun; Ulfi Arvina; Fatmawati, Fatmawati; Meily Meliyani; Nadia Mutmainnah; Asrah Anjani; Sri Putri Wahyuni; Annisa Nurul Fajri; Aliah Tri Saniyah; Syahratul Janna (CV. ITTC INDONESIA, 2025)
This study aims to examine how the use of digital technology can support the development of empathy and social awareness among children in orphanages. The research was conducted at Sejati Muhammadiyah Orphanage in Makassar using a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that digital media plays a significant role as a tool for social education, a means of expressing empathy, and a platform for children's virtual participation in humanitarian activities. The children demonstrated increased social awareness through the consumption of inspirational content and active involvement in digital-based social campaigns. Furthermore, empowerment through digital skills training and ethical media guidance helped strengthen empathy and social responsibility values. The study concludes that the wise and guided use of technology within the orphanage environment can be an effective strategy for fostering social character among youth in the digital era.